2022
DOI: 10.55446/ije.2021.138
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Date of Transplanting on The Incidence of Rice Leaf Folder Cnaphalocrocis medinalis (Guenée) and its Population Dynamics

Abstract: Field studies were conducted to evaluate the impact of transplanting dates and weather parameters on the incidence of rice leaf folder Cnaphalocrocis medinalis (Guenee). During 2018 kharif season, the first incidence was noticed during 27th standard meteorological week (SMW) irrespective of the transplanting dates, with peak being in the 28th SMW (1.67% damaged leaves/hill). Least damage was observed in 4th date of transplanting (20th July), while maximum incidence was with 20th June transplanting. The correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The number of dead hearts (DH) and/ or white ear heads (WEH) were counted and the percent incidence of stem borer was arrived at by using the formula given by Justin and Preetha (2013). The incidence of leaf folder was recorded based on the percentage of leaf damage calculated as formula given by Kumar et al (1996). Data on various weather parameters, viz., temperature (maximum and minimum), humidity (morning and evening), rainfall and wind speed were recorded at the agrometeorology observatory, College of Agriculture, Balaghat, Madhya Pradesh.…”
Section: Methodsmentioning
confidence: 99%
“…The number of dead hearts (DH) and/ or white ear heads (WEH) were counted and the percent incidence of stem borer was arrived at by using the formula given by Justin and Preetha (2013). The incidence of leaf folder was recorded based on the percentage of leaf damage calculated as formula given by Kumar et al (1996). Data on various weather parameters, viz., temperature (maximum and minimum), humidity (morning and evening), rainfall and wind speed were recorded at the agrometeorology observatory, College of Agriculture, Balaghat, Madhya Pradesh.…”
Section: Methodsmentioning
confidence: 99%
“…Pigeon pea pod fly M. obtusa (Malloch) is a more detrimental pest and infests 12 to 100 per cent pods. The pod fly emerged as a key pest and causing10 to 80 per cent damage (Kumar et al, 2003) and estimated to cause a monitory annual loss of US$256 million (Arbind et al, 2013). It was observed that the damage of 22.5%, 21% and 13.2% in North India, Central India and South India, respectively, (Lateef et al, 1981).…”
Section: Introductionmentioning
confidence: 99%